A state assessment of private lands wildlife conservation in the United States - John J. Morgan; Cody M. Rhoden; Bill White; Steven P. Riley (Wildlife Society Bulletin)
ABSTRACT Wildlife habitat in the United States is largely owned by private entities. Threatened and endangered species conservation and game‐species hunting interests occur predominately on private lands. Our wildlife conservation history was characterized by eras of exploitation followed by conservation reactions. State wildlife agencies evolved through those eras as well. We sought to assess state wildlife agency investments in private lands conservation. We used a short survey to construct an index score designed to measure the state agency manpower commitment (%) as it relates to the composition of the state's private ownership (%). During 2019, we collected data about state wildlife agency participation in private lands program activities including cost‐share, equipment loans, or free supplies (seed or herbicide). Our survey metrics showed Kansas, USA, was the national leader in its commitment to private land management. Several midwestern and western states were notably well‐positioned to deliver private lands conservation relative to the nation. Our data show states are trending toward more effort on privately owned lands, but they continue to focus disproportionately more manpower on publicly owned lands or other priorities. Development of state wildlife agency commitments to private lands is a process characterized well by the Missouri Department of Conservation, USA. Expansion in conservation efforts on private lands will likely be linked to funding expansion that includes nonconsumptive users. We charge professionals to meet the conservation challenges of the 21st Century, they must invest significantly greater resources in private lands management through state wildlife agencies. © 2019 The Wildlife Society.